Comprehensive effect of grain size and original target morphology on sputtering behavior of magnetron sputtering target. (April 2023) - Yi, Chen-Xi; Zhang, Hao-Tian; Wang, Shuai-Kang; Han, Gui-Sheng; Liu, Zhi-Ling; Tian, Ye-Fei; Bao, Ming-Dong
Abstract: In this paper, the etching morphology, surface roughness, target voltage, and light emission line intensity of the copper target were investigated using a closed-field unbalanced magnetron sputtering system equipped with optical emission spectroscopy monitor (OEM). The results show that the morphology of the sputtering zone, the target voltage value, the surface roughness, and the OEM value are significantly correlated with the grain size of the target. After sputtering, the original target's morphology dramatically influences the surface roughness and OEM value. Highlights: The surface morphology of the target after sputtering is related to the grain size. The target voltage value follows the order: V (30 μm target) < V(60 μm target) < V(150 μm target). The film morphology is affected by target grain size and target voltage.